Answer:
Option: D is the correct answer.
D. The exponential function decays at three-fourths the rate of the quadratic function.
Step-by-step explanation:
The graph of exponential function passes through (-2,4) and (0,1).
The rate of decay is given by:
[tex]\text{Rate\ of\ decay}=|\dfrac{1-4}{0-(-2)}|\\\\\\\text{Rate\ of\ decay}=|\dfrac{-3}{2}|\\\\\\\text{Rate\ of\ decay}=\dfrac{3}{2}[/tex]
and the graph of quadratic function passes through (-2,4) and (0,0).
The rate of decay is given by:
[tex]\text{Rate\ of\ decay}=|\dfrac{0-4}{0-(-2)}|\\\\\\\text{Rate\ of\ decay}=|\dfrac{-4}{2}|\\\\\\\text{Rate\ of\ decay}=2[/tex]
Hence, the rate of decay of exponential function decays at three-fourths the rate of the quadratic function.
( since,
[tex]2\times \dfrac{3}{4}=\dfrac{3}{2}[/tex]
i.e.
rate of decay of quadratic function×(3/4)=Rate of decay of exponential function )